Perlindungan Hukum Pemegang Hak Atas Tanah Dalam Kasus Sertifikat Ganda - Saputra, Anugerah Yudha; Sukarna, Kadi; Soegianto, Soegianto; Sofyan, Syafran (Universitas Semarang, 2024)
This research aims to analyze the forms of legal protection for land rights holders and legal actions in cases of double certificates. The urgency of this research is to analyze the forms of legal protection for land rights holders in cases of double certificates, which often threaten legal certainty and cause social conflicts due to administrative negligence and land mafia practices, thus requiring strict legal efforts and comprehensive solutions. The type of research used is normative juridical with qualitative data processing. The data sources used in the research are primary data in the form of interviews and secondary data. The results of this study explain that the PTUN decision on the double certificate dispute case Number: 35/G/2021/PTUN.SMG dated September 2, 2021, which has permanent legal force, is 1). The appellant's request was fully granted because, based on the judge's consideration and through the administrative examination mechanism, it was proven that the appellant is the actual landowner with the legal basis of Building Use Rights Certificate (SHGB) Number 1385/Village of Sambirejo in the name of Elisa Mariani Wijaya and Ownership Rights Certificate (SHM) Number 2709/Village of Sambirejo in the name of Hartono Widjaja, which were issued in 1995; 2). In that case, the legal action taken by the BPN was the mediation effort in accordance with Article 43 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning the Handling and Settlement of Land Cases. Penelitian ini bertujuan untuk menganalisis bentuk perlindungan hukum bagi pemegang hak atas tanah dan tindakan hukum dalam sertifikat ganda. Urgensi penelitian ini adalah untuk menganalisis bentuk perlindungan hukum bagi pemegang hak atas tanah dalam kasus sertifikat ganda, yang sering kali mengancam kepastian hukum dan menimbulkan konflik sosial akibat kelalaian administratif dan praktik mafia tanah, sehingga diperlukan upaya hukum yang tegas dan solusi yang komprehensif. Jenis penelitian yang digunakan adalah yuridis normatif dengan pengolahan data secara kualitatif, Sumber data yang digunakan dalam penelitian adalaha data primer berupa wawancar dan data sekunder. Hasil penelitian ini menjelaskan bahwa putusan PTUN sengketa kasus sertifikat ganda Nomor: 35/G/2021/PTUN.SMG tanggal 2 September 2021 dan telah berkekuatan hukum tetap adalah 1). Permohonan Penggunggat dikabulkan seluruhnya dikarenakan dengan pertimbangan hakim dan melalui mekanisme uji administrasi membuktikan bahwa Penggunggat adalah pemilik tanah yang sebenarnya dengan alas hak Sertifikat Hak Guna Bangunan (SHGB) Nomor 1385/Kelurahan Sambirejo atas nama Elisa Mariani Wijaya dan Sertifikat Hak Milik (SHM) Nomor 2709/Kelurahan Sambirejo atas nama Hartono Widjaja, yang diterbitkan pada Tahun 1995; 2). Pada kasus tersebut tindakan hukum yang dilakukan oleh BPN adalah dilakukannya upaya mediasi yang sesuai dengan Pasal 43 Peraturan Menteri Agraria Dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 21 Tahun 2020 tentang Penanganan Dan Penyelesaian Kasus Pertanahan.